2022
DOI: 10.1063/5.0095354
|View full text |Cite
|
Sign up to set email alerts
|

Propagation, mixing, and turbulence characteristics of saline and turbidity currents over rough and permeable/impermeable beds

Abstract: A series of constant-flux saline and turbidity current experiments were carried out, focusing on the coupling impact of bed roughness and permeability on current propagation, mixing, and turbulence characteristics. The distinct current propagation phases on RI (rough and impermeable) and RP (rough and permeable) beds are identified respectively. Experimental results revealed that intermittently undulating bed surface breaks the strict no-slip boundary, thereby increasing local current velocity near the bed, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…For the bare‐slope condition (Figure 7a, run 1), the TKE profile of the turbidity current without sediment deposition satisfies a bimodal distribution. In general, the upper TKE peak locates at the current‐ambient fluid interface, and the lower TKE peak is close to the bed surface, which is consistent with previous studies (Baas et al., 2004, 2005; He et al., 2022). The effect of vegetation height α on the TKE profiles is only manifested in the upper peaks (Figure 7a, runs 1, 2, and 4).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For the bare‐slope condition (Figure 7a, run 1), the TKE profile of the turbidity current without sediment deposition satisfies a bimodal distribution. In general, the upper TKE peak locates at the current‐ambient fluid interface, and the lower TKE peak is close to the bed surface, which is consistent with previous studies (Baas et al., 2004, 2005; He et al., 2022). The effect of vegetation height α on the TKE profiles is only manifested in the upper peaks (Figure 7a, runs 1, 2, and 4).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, the friction velocity of the slope surface uz=0 ${u}_{z=0}^{\ast }$ is obtained through an appropriate linear extrapolation as was done by He et al. (2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These frequent and diverse occurrences of gravity currents in the natural environment have motivated numerous investigations, of interdisciplinary nature, of these gravity flows. Several studies have shown how the propagation of dense, bottom gravity currents is affected by topographic aspects [15][16][17][18][19][20][21][22] , by sloping boundaries [23][24][25][26][27][28][29][30][31] as well as rapidly changing slopes [32][33][34][35] . Most of these studies have focused on the mean flow dynamics and the related entrainment of ambient fluid that strongly affects the flow development and fluid properties.…”
Section: Introductionmentioning
confidence: 99%